Defining ambulatory care sensitive conditions for adults in Portugal - João Sarmento; João Victor Muniz Rocha; Rui Santana (BMC, 2020)
Abstract Background Ambulatory Care Sensitive Conditions (ACSCs) are health conditions for which adequate management, treatment and interventions delivered in the ambulatory care setting could potentially prevent hospitalization. Which conditions are sensitive to ambulatory care varies according to the scope of health care services and the context in which the indicator is used. The need for a country-specific validated list for Portugal has already been identified, but currently no national list exists. The objective of this study was to develop a list of Ambulatory Care Sensitive Conditions for Portugal. Methods A modified web-based Delphi panel approach was designed, in order to determine which conditions can be considered ACSCs in the Portuguese adult population. The selected experts were general practitioners and internal medicine physicians identified by the most relevant Portuguese scientific societies. Experts were presented with previously identified ACSC and asked to select which could be accepted in the Portuguese context. They were also asked to identify other conditions they considered relevant. We estimated the number and cost of ACSC hospitalizations in 2017 in Portugal according to the identified conditions. Results After three rounds the experts agreed on 34 of the 45 initially proposed items. Fourteen new conditions were proposed and four achieved consensus, namely uterine cervical cancer, colorectal cancer, thromboembolic venous disease and voluntary termination of pregnancy. In 2017 133,427 hospitalizations were for ACSC (15.7% of all hospitalizations). This represents a rate of 1685 per 100,000 adults. The most frequent diagnosis were pneumonia, heart failure, chronic obstructive pulmonary disease/chronic bronchitis, urinary tract infection, colorectal cancer, hypertensive disease atrial fibrillation and complications of diabetes mellitus. Conclusions New ACSC were identified. It is expected that this list could be used henceforward by epidemiologic studies, health services research and for healthcare management purposes. ACSC lists should be updated frequently. Further research is necessary to increase the specificity of ACSC hospitalizations as an indicator of healthcare performance.